Epidemiological and economic burden of metabolic syndrome and its consequences in patients with hypertension in Germany, Spain and Italy; a prevalence-based model - Scholze Jürgen; Alegria Eduardo; Ferri Claudio; Langham Sue; Stevens Warren; Jeffries David; Uhl-Hochgraeber Kerstin (BMC, 2010)
Abstract Background The presence of metabolic syndrome in patients with hypertension significantly increases the risk of cardiovascular disease, type 2 diabetes and mortality. Our aim is to estimate the epidemiological and economic burden to the health service of metabolic syndrome in patients with hypertension in three European countries in 2008 and 2020. Methods An age, sex and risk group structured prevalence based cost of illness model was developed using the United States Adult Treatment Panel III of the National Cholesterol Education Program criteria to define metabolic syndrome. Data sources included published information and public use databases on disease prevalence, incidence of cardiovascular events, prevalence of type 2 diabetes, treatment patterns and cost of management in Germany, Spain and Italy. Results The prevalence of hypertension with metabolic syndrome in the general population of Germany, Spain and Italy was 36%, 11% and 10% respectively. In subjects with hypertension 61%, 22% and 21% also had metabolic syndrome. Incident cardiovascular events and attributable mortality were around two fold higher in subjects with metabolic syndrome and prevalence of type 2 diabetes was around six-fold higher. The economic burden to the health service of metabolic syndrome in patients with hypertension was been estimated at €24,427, €1,900 and €4,877 million in Germany, Spain and Italy and forecast to rise by 59%, 179% and 157% respectively by 2020. The largest components of costs included the management of prevalent type 2 diabetes and incident cardiovascular events. Mean annual costs per hypertensive patient were around three-fold higher in subjects with metabolic syndrome compared to those without and rose incrementally with the additional number of metabolic syndrome components present. Conclusion The presence of metabolic syndrome in patients with hypertension significantly inflates economic burden and costs are likely to increase in the future due to an aging population and an increase in the prevalence of components of metabolic syndrome.